Patient and Provider Satisfaction With a Geomapping Tool for Finding Community Family Physicians in Ontario, Canada: Cross-Sectional Online Survey Study. - Belanger, Christopher; Peixoto, Cayden; Francoeur, Sara; Bjerre, Lise M. (JMIR formative research, 2024)
Background: Language-concordant health care, or health care in a patient’s language of choice, is an important element of health accessibility that improves patient safety and comfort and facilitates an increased quality of care. However, prior research has found that linguistic minorities often face higher travel burdens to access language-concordant care compared to the general population. Objective: This study intended to assess patient experiences and satisfaction with an online interactive physician map that allows patients to find family physicians who speak their preferred language in and around Ottawa, Ontario, Canada, as a means of identifying areas of improvement. Methods: This study used an online survey with questions related to user satisfaction. Responses to Likert-scale questions were compiled as summary statistics and short-answer responses underwent thematic analysis. The study setting was Ottawa and Renfrew County, Ontario, and the surrounding region, including the province of Quebec. Results: A total of 93 respondents completed the survey and self-identified as living in Ontario or Quebec. Overall, 57 (61%) respondents were “very satisfied” or “somewhat satisfied” with the map, 16 (17%) were “neither satisfied nor dissatisfied,” and 20 (22%) were “very dissatisfied” or “somewhat dissatisfied.” We found no significant differences in satisfaction by preferred language, age group, physician attachment, or intended beneficiary. A total of 56 respondents provided short-answer responses to an open-ended question about map improvements. The most common specific suggestion was to show which physicians are accepting new patients (n=20). Other suggestions included data refreshes (n=6), user interface adjustments (n=23), and additional languages (n=2). Some participants also provided positive feedback (n=5) or expressed concern with their inability to find a family physician (n=5). Several comments included multiple suggestions. Conclusions: While most patients were satisfied with the online map, a significant minority expressed dissatisfaction that the map did not show which family physicians were accepting new patients. This suggests that there may be public interest in an accessible database of which family physicians in Ontario are currently accepting new patients.

Évaluer le potentiel de soins linguistiquement concordants pour les francophones de l’Ontario : une étude populationnelle transversale. - Carr, Kady; Batista Moliner, Ricardo; Fitzgerald, Michael; Lamontagne, Sophie; Bader Eddeen, Anan; Timony, Patrick E.; Bédard, Daniel; Gauthier, Alain; Prud’homme, Denis; Landry, Josette-Renée; Chomienne, Marie-Hélène; Denis-Leblanc, Manon; et al. (Minorités linguistiques et société, 2024)
Cette étude a utilisé les données sur les médecins, la facturation et le recensement de 2016 dont dispose l’ICES pour examiner l’accès potentiel à des médecins de famille francophones pour les francophones résidant dans 1 643 aires de diffusion agrégées (ADA) de l’Ontario. L’Ontario compte 550 280 francophones, soit 4,1 % de sa population. Nous avons identifié 8 199 médecins de famille, parmi lesquels 1 169 se sont autodéclarés francophones. Le ratio provincial global pour les francophones était de 2,12 médecins par 1 000 résidentes et résidents, comparativement à un ratio de 0,66 pour les anglophones. Dans les ADA où les francophones étaient majoritaires, le ratio pour les francophones était inférieur au ratio pour les anglophones (0,63 vs 2,02), alors que dans toutes les autres ADA, le ratio francophone était plus élevé (3,46 vs 0,62 dans les 83,4 % des ADA où les francophones représentaient >0 % à <5 % de la population). Huit ADA du Nord-Est et de l’Est de l’Ontario présentaient un déficit relatif important de médecins de famille francophones par rapport au ratio provincial. Ces résultats donnent un aperçu des régions qui pourraient bénéficier de programmes visant à éliminer les barrières linguistiques. Mots-clés : Concordance linguistique, médecins de famille, accès aux soins primaires, francophones, Ontario

L'effectivité des lois linguistiques dans le secteur de la santé - Forgues, Éric; Maillet, Stéphanie (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
Cet article découle d’une étude qui problématise le concept d’effectivité des lois linguistiques. Dans cette étude, nous cherchions à mieux comprendre les dimensions juridiques, sociales, organisationnelles et psychologiques qui peuvent agir sur l’effectivité des lois linguistiques dans le secteur de la santé dans les provinces du Canada qui disposent de telles lois. Sachant que les professionnels de la santé sont en première ligne pour offrir des services en français, nous avons analysé leurs perceptions en ce qui concerne divers aspects pouvant influencer l’offre de services en français. Les résultats montrent que des différences souvent significatives s’observent entre les répondantes et les répondants anglophones et francophones et ceux qui oeuvrent dans des hôpitaux anglophones et francophones. Les résultats révèlent également que des efforts doivent se poursuivre pour atteindre une effectivité accrue, tout en offrant des pistes pour mieux orienter ces efforts. Mots-clés : effectivité des lois linguistiques, santé en français, francophonie, langue de service, minorités linguistiques

Language barriers and healthcare access: a qualitative study in the Volta Region of Ghana - Glover-Meni, Nathaniel; Nyarko, Joy Ato; Agbezorlie, Peter K.; Agyei, Dominic Dankwah (Journal of Communication in Healthcare, 2024)
Background The study explores the language barriers between two language minority populations and healthcare professionals in the Volta Region of Ghana. Methods An interpretive description with a qualitative approach to data collection and analysis was used. This study was carried out in the Tafi-Atome and Avatime-Vane communities, the Hohoe Municipal Hospital and the Margaret Marquart Catholic Hospital in the Kpando Municipality. In all, 46 respondents comprising 19 purposively sampled community members (patients) from the two selected communities and 27 conveniently sampled healthcare professionals from the two health facilities were interviewed. The face-to-face in-depth interviews were audio-recorded, transcribed and thematically analysed. Results The study revealed a barrier in language use between healthcare professionals and patients from the two language minority communities. While healthcare professionals preferred to use English, Akan and Ewe, the patients, on the other hand, preferred their native languages, which are Sideme and Tegbor. The services of unqualified interpreters were utilised by both healthcare professionals and patients. Study participants were aware of these challenges, which prevented the patients from receiving optimum healthcare services, and the healthcare workers from delivering client-centred healthcare services. Conclusions The presence of communication challenges emanating from language barriers between healthcare professionals and patients should be considered as a key hindrance to the attainment of the Sustainable Development Goal Three (SDG3), which aims to promote health and well-being at all ages. Therefore, stakeholders in the healthcare delivery system in Ghana need to prioritize stronger communication and translation practices and policies.

L’accès aux services en français, de la connaissance des défis à l’accompagnement des organisations vers le changement. - Savard, Sébastien; Savard, Jacinthe; Sauvé-Schenk, Katrine; van Kemenade, Solange; Benoît, Josée (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
Depuis 2011, le Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (GReFoPS) cherche à mieux comprendre les facilitateurs et les obstacles à l’offre de services en français dans un contexte linguistique minoritaire au Canada. Dans cet article, les auteurs présentent un bilan de près de 12 ans de recherche sur le sujet, en décrivant les facteurs individuels et organisationnels qui influencent l’offre de services en français. Les résultats de ces études ont mis en lumière quelques mécanismes organisationnels ou interorganisationnels qui ont permis l’émergence de pratiques novatrices pour améliorer l’offre de services en français dans les services communautaires et institutionnels. On y décrit également des outils créés pour aider les gestionnaires de ces services à identifier des mesures et des mécanismes pouvant répondre aux besoins des usagers francophones en situation minoritaire. Mots-clés : accès, services sociaux et de santé, francophones, contexte minoritaire, Canada